Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Di Sekitar Objek Wisata Candi Muaro Jambi - Anissa Anggraini; Arsa Arsa; Nurlia Fusfita (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to find out and analyze the factors that affect the income of traders around the Muaro Jambi Temple Attraction. This research using quantitative descriptive methods aims to systematically describe the facts or characteristics of a particular population or a particular field factually and meticulously. The population used in this study was 30 traders who were active in Muaro Jambi Temple. The results of the capital study affect the income level of traders in Muara Jambi Temple, the results of partial testing showed significant results stating that there was a significant influence between the capital variable (X1) on income (Y). the length of the undertaking affects the level of income of the trader. partial testing states that there is no significant effect of the Variable Length of Business (X2) on the income of (Y) traders. time allocation affects the level of income of traders. partial testing stated that there was no significant influence of the Time Allocation variable (X3) on the income of (Y) traders in Muaro Jambi Temple. there is a significant influence between the variables of Capital (X1) on income (Y). there is no significant effect on the variable Length of Business (X2) on revenue (Y). there was no significant effect of the Time Allocation variable (X3) on revenue (Y).